A novel 1p33p32.2 deletion involving SCP2, ORC1, and DAB1 genes in a patient with craniofacial dysplasia, short stature, developmental delay, and leukoencephalopathy: A case report. Issue 45 (6th November 2020) - Jiang, Maoying; Wang, Shanlin; Li, Fei; Geng, Juan; Ji, Yiting; Li, Ke; Jiang, Xiaodong
Abstract: Introduction: Microdeletion syndromes occur from deletion of 5Mb of a chromosome in approximately 5% of patients with unexplained intellectual disability. Interstitial microdeletions at bands 1p33 and 1p32.2 of the short arm of chromosome 1 are rare and have not been previously reported in relation to disease. Patient concerns: We present a case of a 39-month boy with Pierre Robin sequence, development delay/intellectual disability, growth retardation, short stature, leukoencephalopathy, craniofacial dysplasia, and speech delay. The child was referred to the Child health care department in October 2014 for his delayed language development and aggravated aggression. Diagnosis: Molecular diagnostic testing with G-band karyotyping was normal but clinical microarray analysis detected a 10 Mb microdeletion at 1p33p32.2. Interventions: The patient received rehabilitation. Outcomes: Three candidate genes were pinpointed to the deleted area, including ORC1, SCP2, and DAB1 . Phenotype-genotype analysis suggested that these three genes are likely to be responsible for the main phenotypes observed in the patient, such as microcephaly, growth retardation, short stature, leukoencephalopathy, and development delay/intellectual disability. Conclusions: The spectrum of phenotypes this case presented with are likely to be caused by 1p33p32.2 deletion which could represent a new microdeletion syndrome.